2014
DOI: 10.1039/c4nr03275f
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant chemistry of graphene-based materials and its role in oxidation protection technology

Abstract: Two-dimensional nanomaterials have potential as a new class of antioxidants that combine physical barrier function with ultrahigh surface area for free radical scavenging. This work presents the first measurements of the chemical reactivities of graphene-based materials toward a set of model free radicals and reactive oxygen species using electron paramagnetic resonance spectroscopy (EPR) and sacrificial dye protection assays. Graphene-based materials are shown to protect a variety of molecular targets from ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
251
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(264 citation statements)
references
References 85 publications
8
251
0
5
Order By: Relevance
“…Those studies suggested that both physical and chemical adsorption can occur when free radicals approach to the graphene surface. The radical scavenging activity of graphene-based materials towards hydroxyl, superoxide and other model free radicals of sufficient stability has also been proven recently by several experimental works [18,19]. For instance, Qiu et al [18] found that graphene exhibits significant antioxidant activity in the form of hydroxyl and superoxide radical scavenging, which may be associated with the pristine sp 2 carbon domains on basal surfaces.…”
Section: Introductionmentioning
confidence: 95%
“…Those studies suggested that both physical and chemical adsorption can occur when free radicals approach to the graphene surface. The radical scavenging activity of graphene-based materials towards hydroxyl, superoxide and other model free radicals of sufficient stability has also been proven recently by several experimental works [18,19]. For instance, Qiu et al [18] found that graphene exhibits significant antioxidant activity in the form of hydroxyl and superoxide radical scavenging, which may be associated with the pristine sp 2 carbon domains on basal surfaces.…”
Section: Introductionmentioning
confidence: 95%
“…They also provide an effective conducting network for electron transfer, massive pore structures for ion transport, and large surface areas for reaction. In addition, they scavenge reactive oxygen species [19][20][21][22][23][24][25][26] to enhance the catalyst stability. 8 When synthesized on the scaffolds of carbon nanostructures, it has been demonstrated that the electrocatalytic Ni oxide-based nanomaterials possess high performance for hydrogen and oxygen evolution.…”
mentioning
confidence: 99%
“…Such noticeable increase of burning rate is associated with good activity and high specific surface area from activated carbon CRH-KOH, which is almost 3000 m 2 /g. The surface and the edges of activated carbon have many defects, which can act as a matrix for the formation and stabilization of free radicals (OH radicals) [13], which are formed during the decomposition of nitric acid, is described in following reaction and were proposed by T.B. Brill, and Y.J.…”
Section: The Combustion Experiments In Strand Burnermentioning
confidence: 99%